Footloose (2011) [videorecording (DVD)] - Brewer, Craig; MacDowell, Andie; Wormald, Kenny, 1984-; Teller, Miles; Flueger, Patrick, 1983-; Colon, Ziah; Quaid, Dennis; Hough, Julianne, 1988- (Paramount Home Entertainment, 2011)
The is the remake of the 1984 original film that starred Kevin Bacon. Ren MacCormack moves from Boston to the small town of Bomont, where he experiences a heavy dose of culture shock. A few years prior, the community was rocked by a tragic accident that killed five teenagers after a night out. Bomont's councilmen and the beloved Reverend Shaw Moore responded by invoking ordinances that prohibit loud music and dancing. Not one to bow to the status quo, Ren challenges the ban, revitalizes the town, and falls in love with the minister's troubled daughter, Ariel.